2014
DOI: 10.1016/j.jhydrol.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-pressure dynamics above an oscillating water table

Abstract: This paper presents a sand column dataset on the soil moisture-pressure dynamics above a simple harmonic oscillating water table. A total of 19 experiments were conducted in which all experimental parameters were held constant except for the oscillation period which ranged between 12.25 hours down to 10 seconds. The data show clear evidence of hysteresis at longer oscillation periods where the unsaturated zone has sufficient time to adjust to the water table motion. At shorter periods the contrary exists with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 16 publications
7
26
1
Order By: Relevance
“…Note that the hydrostatic pressure assumption is consistent with evidences from experiments on low-frequency water table fluctuations (Cartwright, 2014). In this study, we also considered low-frequency fluctuations such as tide and thus made the same assumption, i.e., neglecting the vertical flow in the vadose zone.…”
Section: Flow In the Vadose Zonesupporting
confidence: 64%
See 1 more Smart Citation
“…Note that the hydrostatic pressure assumption is consistent with evidences from experiments on low-frequency water table fluctuations (Cartwright, 2014). In this study, we also considered low-frequency fluctuations such as tide and thus made the same assumption, i.e., neglecting the vertical flow in the vadose zone.…”
Section: Flow In the Vadose Zonesupporting
confidence: 64%
“…This model setup is consistent with the conditions of natural coastal aquifers to some extent. The coastal aquifer response C AR (K s =Bx) number was calculated to be 3.43, corresponding to cases of low-frequency oscillations (Li et al, 2000b;Cartwright, 2014).…”
Section: Model Validationmentioning
confidence: 99%
“…Comparisons between measured and simulated surface water content showed that hysteresis exerts significant influence on surface moisture content dynamics, especially when the water table is close to land surface. Cartwright [] showed evidence of hysteresis at longer oscillation periods with a sand column tests on the soil moisture‐pressure dynamics above an oscillating water table.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments showed that hysteresis effect altered with fluctuations period variation (Cartwright, ). Strong hysteresis reduces the influence of unsaturated zone on saturated zone and weakens the vertical water exchange between above two zones.…”
Section: Theorymentioning
confidence: 99%
“…(, ) showed better precision compared with traditional Boussinesq models when applied in simulating the wave or tidal induced groundwater wave, the coefficients adopted in the revised models often deviate much away from the actual ones. Some studies have attributed such discrepancy to hysteresis effect, which results in moisture asymmetry during the alternative drying and wetting processes (Stauffer and Kinzelbach, ; Cartwright, ; Shoushtari et al ., ). Furthermore, hysteresis effect has been taken into account in numerical models based on Richard's equations.…”
Section: Introductionmentioning
confidence: 99%